Spatial Analysis of Flood Vulnerability Levels in Makassar City Using Geographic Information Systems - Maru, Rosmini; Nasrul , Nasrul; Nuryadin, Muhammad Taufan; Nur, Medar M; Amdah, Misdar; Hasja, Aulia Diar; Musyawarah, Rahma; Mulianti, Mulianti; Tripaldi, Agus (Universitas Hasanuddin, 2024)
This research aims to determine the flood intensity in Makassar City, which is influenced by several factors, including land use, slope gradient, land cover, and rainfall. The research method is a quantitative approach using spatial analysis to examine spatial phenomena. The spatial analysis was conducted using an overlay method with a scoring technique to map each variable that affects flood intensity. The analysis results indicate that the flood intensity in Makassar City is categorized into three levels: low, moderate, and high.. The analysis results suggest that in Makassar City, 37.4 km² or 21% of the total area falls into the low rainfall intensity category. In contrast, the moderate rainfall intensity category encompasses 73.3 km² or 41% of the city, while the high rainfall intensity category represents 68.1 km² or 38% of the total area. This research has implications for efforts to control the pace of regional development that influences and potentially exacerbates flooding, thereby enabling early mitigation of environmental issues.